FOOD SOVEREIGNTY: peoples' right - Miranda, Raul [UNESP] (Univ Taubate, 2021)
The basic right to food is historically denied to a large part of humanity. This article intends to demonstrate that its guarantee depends on a strong and wide confrontation with the practices and discourses of the dominant agents of the capitalist agro-food system. This counter-hegemonic process has been taking place in a field of struggles led by social movements that raise the banner of food sovereignty. This flag, in addition to guaranteeing food security, provides the accumulation of forces for the conquest of human rights as a whole. The performance of Latin American peoples has shown the power of agroecology as an important instrument of these struggles, by enabling the dignified condition of an autonomous peasant in the face of the expropriation of capital. Finally, the article argues about the need for a democratization of access to land that guarantees its use for the production of healthy food and the conservation of ecological functions, as this proves to be a central issue not only for rural populations, but for the survival of the working class.
Keywords: Food sovereignty; Social movements; Agroecology; Human rights; Peasantry